The immunomodulatory mechanism of acupuncture treatment for ischemic stroke: research progress, prospects, and future direction - Kuang, Hongjun; Zhu, Xinzhou; Chen, Huan; Tang, Han; Zhao, Hong (Frontiers in Immunology, 2024)
Ischemic stroke (IS) is one of the leading causes of death and disability. Complicated mechanisms are involved in the pathogenesis of IS. Immunomodulatory mechanisms are crucial to IS. Acupuncture is a traditional non-drug treatment that has been extensively used to treat IS. The exploration of neuroimmune modulation will broaden the understanding of the mechanisms underlying acupuncture treatment. This review summarizes the immune response of immune cells, immune cytokines, and immune organs after an IS. The immunomodulatory mechanisms of acupuncture treatment on the central nervous system and peripheral immunity, as well as the factors that influence the effects of acupuncture treatment, were summarized. We suggest prospects and future directions for research on immunomodulatory mechanisms of acupuncture treatment for IS based on current progress, and we hope that these will provide inspiration for researchers. Additionally, acupuncture has shown favorable outcomes in the treatment of immune-based nervous system diseases, generating new directions for research on possible targets and treatments for immune-based nervous system diseases.